Cavitation - Birk Lothar (Fundamentals of Ship Hydrodynamics, 2019)
This chapter discusses the cavitation phenomenon, where it is likely to occur, and which negative effects it can have. It describes about detrimental effects of cavitation and the likelihood of cavitation with cavitation numbers. Cavitation is identified by visual appearance and location. In marine systems, propellers and lifting foils especially are subject to the cavitation phenomena. Cavitation may also occur in pumps and piping systems. One objective in the design of hydrodynamic systems is the avoidance or at least the delay of cavitation. Vessels with relatively large propellers, which leave only a minimum of clearance between blade tip and hull, sometimes experience propeller‐hull cavitation. The highly unsteady nature of cavitation with constant production and collapses of cavities creates high pressure shock waves which are capable of exciting propeller blades, rudder, and nearby hull plating to measurable vibrations.